Characterization of cellular oxidative stress response by stoichiometric redox proteomics - Zhang, Tong (Am J Physiol Cell Physiol, 2021)
The thiol redox proteome refers to all proteins whose cysteine thiols are subjected to various redox-dependent posttranslational modifications (PTMs) including S-glutathionylation (SSG), S-nitrosylation (SNO), S-sulfenylation (SOH), and S-sulfhydration (SSH). These modifications can impact various aspects of protein function such as activity, binding, conformation, localization, and interactions with other molecules. To identify novel redox proteins in signaling and regulation, it is highly desirable to have robust redox proteomics methods that can provide global, site-specific, and stoichiometric quantification of redox PTMs. Mass spectrometry (MS)-based redox proteomics has emerged as the primary platform for broad characterization of thiol PTMs in cells and tissues. Herein, we review recent advances in MS-based redox proteomics approaches for quantitative profiling of redox PTMs at physiological or oxidative stress conditions and highlight some recent applications. Considering the relative maturity of available methods, emphasis will be on two types of modifications: 1) total oxidation (i.e., all reversible thiol modifications), the level of which represents the overall redox state, and 2) S-glutathionylation, a major form of reversible thiol oxidation. We also discuss the significance of stoichiometric measurements of thiol PTMs as well as future perspectives toward a better understanding of cellular redox regulatory networks in cells and tissues.